THE INFLUENCE OF ABUTMENT SURFACE TREATMENT ON PULL-OFF BOND STRENGTH BETWEEN (5)YTTRIA STABILIZED ZIRCONIA CROWN AND TITANIUM IMPLANT ABUTMENT (Mustansiria Dental Journal, 2024)
Aim: The objective of this research was to evaluate the effect of mechanical method and energetic method of surface treatments for Ti-abutment base (Ti-Base, Dentium/Korea) on the pull-off  bond strength with (5)Y-TZP crown. Materials and Methods: Forty titanium implant abutments were used in this study and randomly assigned to four groups (n = 10 for each group) according surface treatment methods of titanium abutment: group (1) act as control without surface treatment for Ti-abutment, group (2) bur surface treatment of Ti-abutment, group (3) sandblast (50-µm aluminum oxide) surface treatment for Ti-abutment, group (4) plasma surface treatment for Ti-abutment. Then, forty implant analogs were placed in the center of acrylic mold. After that abutment was tightened on the each analog with (35 N/cm) torque . Forty (5)Y-TZP crowns fabricated by CAD/CAM system that had special design with  occlusal O-hole cemented to all abutments using Allcem dual-cure resin cement. All specimens were then subjected to thermos-cycling with (5000) cycles. With a universal testing machine record pull-off  bond strength for all samples, Collected data were analyzed using a one-way analysis of variance at a significance level of (p < 0.01) . Results: The bur treated abutment (group 2)  group showed the highest bond strength values, followed by sandblast treated abutment (group 3) and plasma treated abutment (group 4). Control group was the lowest value of tensile strength. Conclusion: Surface treatments of Ti-abutment  had observed effect on pull-off (tensile bond strength) between Ti-abutment and (5)Y-TZP crown Bur and sandblast cause roughness of surface and increase bond strength , plasma cause reactive surface for increasing tensile bond strength.